KLASTER CURAH HUJAN TRMM RATA-RATA 3 JAM-AN DAN HUBUNGANNYA DENGAN FENOMENA ATMOSFER - Ina Juaeni; Bambang Siswanto; - Nurzaman; - Martono; Farid Lasmono (Jurnal Sains Dirgantara, 2011)
Three hourly Tropical Rainfall Measuring Mission (TRMM) rainfall data availability provides an opportunity to study more deeply in short time atmospheric process, as is presented in this paper. Arithmatic mean value of rainfall is used to eliminate micro and local factors. Clustering with annual average data show the number of clusters varies from 6 to 14. The number of the smallest cluster of 6 occurred in 2004, while the number of the highest clusters found in 2010. Identify the relationship of 3-hourly rainfall clusters with an atmospheric phenomenon carried out by evaluating the correlation between the number of clusters with Sea Surface Temperature (SST) anomalies in the Pacific and Indian oceans. The results showed clusters number unrelated to SST anomaly in Indian ocean and linearly related to SST anomaly in the Pacific ocean when SST anomalies in the ocean are changing the three hourly accumulative rainfall. Key words:Three hourly, Rainfall, Cluster, SST anomaly